2016
DOI: 10.1007/s10113-016-0928-0
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and drivers of forest cover change in the post-socialist era in Croatia: evidence from a mixed-methods approach

Abstract: Extensive forests in Croatia represent an important biological and economic resource in Europe. They are characterized by heterogeneity in forest management practices dating back to the socialist planned economy of the pre-1991 era. In this study we investigated the difference in rates of deforestation and reforestation in private and state owned forests during the post-socialist period, and the causal drivers of change. The selected region of Northern Croatia is characterised by a high percentage of privately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 31 publications
3
15
0
1
Order By: Relevance
“…Inappropriate land management led to a loss of fertile soil which later caused the abandonment of agricultural land and reforestation (Cebecauer and Hofierka, 2008). The increase in natural vegetation in the lowlands was mostly recorded in the floodplain area of the river Drava, which is in accordance with the results of research in Krapina-Zagorje County (Cvitanović et al, 2016). Soil fertility in the floodplains decreased due to the occurrence of marshes and frequent flooding.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Inappropriate land management led to a loss of fertile soil which later caused the abandonment of agricultural land and reforestation (Cebecauer and Hofierka, 2008). The increase in natural vegetation in the lowlands was mostly recorded in the floodplain area of the river Drava, which is in accordance with the results of research in Krapina-Zagorje County (Cvitanović et al, 2016). Soil fertility in the floodplains decreased due to the occurrence of marshes and frequent flooding.…”
Section: Discussionsupporting
confidence: 78%
“…Fragmentation and the small area of plots enhanced the spread of natural vegetation, i.e. the process of natural succession or reforestation (Cvitanović et al, 2016). Research in Slovakia showed that frequent changes in the ownership structure of the land, agricultural intensification, and deforestation caused increased erosion in hilly and mountainous areas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…between individual regions within one country (Andronache et al 2017). The variability in forest cover among countries and administrative regions results from different political settings, socioeconomic conditions, ownership structure and management practices in the past and present (Cvitanovic et al 2016, Andronache et al 2017. At a global level, Keenan et al (2015) revealed that forest cover increases with the increasing income of the region or the country, while Crespo Cuaresma et al (2017) revealed a U-shaped relationship between the income per capita and the forest cover of countries.…”
Section: Introductionmentioning
confidence: 99%